Warriors : an Alex Hawke novel - Bell, Ted (Bell, Ted. Alex Hawke novel., 2014)
"Counterspy Alex Hawke is out to find and rescue a kidnapped American scientist as the United States and China get closer and closer to all-out nuclear war in the latest adrenaline-fueled thriller in the New York Times bestselling series"--